Cognitive Behavioral Therapy and Eye Movement Desensitization and Reprocessing in Posttraumatic Stress Disorder - Filiz Izci; Gizem Unveren (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Abstract: Cognitive behavioral therapy (CBT) and eye movement desensitization and reprocessing (EMDR) are from the most common treatment methods that have begun to be used in trauma patients in recent years. With the increased applicability of these treatment models in Post Traumatic Stress Disorder (PTSD) and on other trauma patients success of treatment rate in trauma patients is increasing steadily. In this article, it is tried to review the application forms and effects of EMDR and CBT methods among patients with PTSD which is a commonly seen trauma disorder. It is aimed in this article to emphasize the importance of CBT and a newly treatment EMDR in post-traumatic acute and chronic disorders with multiple psychiatric symptoms. [JCBPR 2017; 6(1.000): 31-38]